Analysis of Artificial Insemination Success Rates and Sustainability in East Kalimantan Province - Kirana Dara Dinanti Adiputra; I Putu Gede Didik Widiarta; Andi Nurmasytha; Desy Raharjo (Warmadewa University Press, 2025)
The reproductive performance of beef cattle in East Kalimantan remains a significant challenge, particularly concerning the success of artificial insemination (AI) in improving herd productivity. As the region aims to boost livestock production, understanding the effectiveness of AI becomes crucial. This study analyzes the success rate of AI in beef cattle in East Kalimantan from 2022 to 2024. Using a quantitative-descriptive approach, secondary data were obtained from the Indonesian National Animal Health Information System (iSIKHNAS) and verified by the Livestock and Animal Health Service Office of the East Kalimantan Provincial Government. The success rate of AI was measured through calving rate (CvR), relative effectiveness of AI compared to natural mating, and the proportion of calving births from both methods. The results show AI calving rates of 25.86% in 2022, 10.10% in 2023, and 45.36% in 2024. The relative effectiveness of AI compared to natural mating increased in 2024, with a ratio of 1.3. The proportion of calving births through AI fluctuated yearly, indicating that while AI adoption is growing, natural mating continues to play a critical role in the reproductive system of beef cattle in East Kalimantan Province.